2019
DOI: 10.1016/j.bandl.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Successful second language learning is tied to robust domain-general auditory processing and stable neural representation of sound

Abstract: There is a great deal of individual variability in outcome in second language learning, the sources of which are still poorly understood. We hypothesized that individual differences in auditory processing may account for some variability in second language learning. We tested this hypothesis by examining psychoacoustic thresholds, auditory-motor temporal integration, and auditory neural encoding in adult native Polish speakers living in the UK. We found that precise English vowel perception and accurate Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(125 citation statements)
references
References 105 publications
9
114
2
Order By: Relevance
“…As for formant discrimination, for example, some could perceive very subtle differences when F2 shifted to a very small degree (e.g., 7 Hz), but the formant acuity of others could be much less sensitive (e.g., 117 Hz). As observed in our precursor research (e.g., Kachlicka et al, 2019;Saito, Kachlicka, et al, 2020), the results of Kolmogorov-Smirnov tests found the pitch and duration discrimination scores to be positively skewed (p < .001, p = .041).…”
Section: L2 Auditory Processing Profilessupporting
confidence: 78%
See 2 more Smart Citations
“…As for formant discrimination, for example, some could perceive very subtle differences when F2 shifted to a very small degree (e.g., 7 Hz), but the formant acuity of others could be much less sensitive (e.g., 117 Hz). As observed in our precursor research (e.g., Kachlicka et al, 2019;Saito, Kachlicka, et al, 2020), the results of Kolmogorov-Smirnov tests found the pitch and duration discrimination scores to be positively skewed (p < .001, p = .041).…”
Section: L2 Auditory Processing Profilessupporting
confidence: 78%
“…To our knowledge, little empirical investigation has been conducted on the relationship between explicit and implicit auditory processing. In the context of postpubertal L2 speech learning, however, Diaz, Mitterer, Broersma, Escera, and Sebastian-Galles (2016) have provided preliminary evidence that behavioral and neurophysiological measures seem to tap into two different constructs of perceptual acuity, and that they can explain independent variance in postpubertal L2 pronunciation learning (see Kachlicka et al, 2019;Saito, Sun, & Tierney, 2019;Sun et al, in press).…”
Section: Discussion Conclusion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the role of auditory processing in L2 acquisition, our precursor work (Kachlicka, Saito, & Tierney, 2019) took an exploratory approach, investigating 40 Polish residents' auditory processing ability (temporal, spectral), diverse immersion profiles (LOR = 1-5 years), and L2 English proficiency (segmental perception, grammaticality judgements).…”
Section: Motivation For Current Studymentioning
confidence: 99%
“…In our research projects involving 300+ second language (L2) English users with a range of L1 backgrounds (Chinese, Japanese, Polish, Spanish) in various contexts (immersion, classroom), auditory acuity scores have been found to account for a medium-to-large amount of variance in L2 comprehension skills (vowel perception, grammaticality judgements) (e.g., Kachlicka, Saito, & Tierney, 2019) and L2 production skills (segmental, suprasegmental, lexical, collocational, and morphosyntactic accuracy) (e.g., Saito, Kachlicka, Sun, & Tierney, 2020;Saito, Macmillan, Kroger, Magne, Takizawa, Kachlicka, & Tierney, forthcoming). Similarly, auditory integration scores have shown significant associations with L2 vowel and prosodic perception proficiency (e.g., Sun, Saito, & Tierney, forthcoming) and L2 phonological and lexicogrammar production proficiency (e.g., Saito, Tran, Suzukida, & Tierney, forthcoming).…”
Section: Melody Reproductionmentioning
confidence: 99%